2015
DOI: 10.3892/ijo.2015.2817
|View full text |Cite
|
Sign up to set email alerts
|

FAM83B is a novel biomarker for diagnosis and prognosis of lung squamous cell carcinoma

Abstract: Personalized therapy for non-small cell lung cancer (NSCLC), particularly lung adenocarcinoma, has recently been significantly improved by the discovery of various molecular targets. However, this has not been the case for lung squamous cell carcinoma (SCC). In the present study, we identified the family with sequence similarity 83, member B (FAM83B) as a candidate marker for SCC through a comprehensive gene expression analysis and examined its correlations with various clinicopathological factors. The subject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
40
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 36 publications
6
40
0
Order By: Relevance
“…Interestingly, elevated FAM83B expression is associated with estrogen-receptor (ER) and progesterone-receptor (PR) negative breast tumors, an aggressive subtype for which currently no targeted therapies exist [22, 64]. In addition, FAM83B mRNA expression is significantly higher in lung squamous cell carcinoma when compared to normal adjacent tissue or adenocarcinoma [24, 65]. This finding led to the recommendation that FAM83B is a biomarker and a prognostic marker, as high expression of FAM83B correlates with poor disease-free survival of patients with lung squamous cell carcinoma [65].…”
Section: A Closer Look At Fam83bmentioning
confidence: 99%
“…Interestingly, elevated FAM83B expression is associated with estrogen-receptor (ER) and progesterone-receptor (PR) negative breast tumors, an aggressive subtype for which currently no targeted therapies exist [22, 64]. In addition, FAM83B mRNA expression is significantly higher in lung squamous cell carcinoma when compared to normal adjacent tissue or adenocarcinoma [24, 65]. This finding led to the recommendation that FAM83B is a biomarker and a prognostic marker, as high expression of FAM83B correlates with poor disease-free survival of patients with lung squamous cell carcinoma [65].…”
Section: A Closer Look At Fam83bmentioning
confidence: 99%
“…DPEP1 expression data were obtained using custom microarray analysis, as previously described (20). Briefly, the surgical specimen was homogenized and mixed with ISOGEN ® reagent (Nippon Gene Co., Ltd., Tokyo, Japan).…”
Section: Clinical Samples Of Patientsmentioning
confidence: 99%
“…Under such circumstances, it is quite important to characterize the subtypes of NSCLC before designing appropriate treatment strategies. Previous studies have demonstrated that follistatin and the family with sequence similarity 83, member B (FAM83B) are candidate biomarkers for lung adenocarcinoma and squamous cell carcinoma, respectively [3,4]. Whether there exist additional potential prognostic biomarkers for different subtypes of NSCLC is of great interest.…”
Section: Introductionmentioning
confidence: 99%